Sistem Kerja Automatic Transfer Switch Dan Automatic Generator Start Di Pt. Garuda Media Telematika - Fatoni, Ahmad; Amin, Baihaqi Ulum; Imamatul Ummah (Universitas Hasyim Asy`ari, 2024)
PT. Garuda Media Telematics is an internet service provider (ISP), this company really needs electrical energy to operate 24 hours a day. However, the electricity source distributed by PLN is not continuously available, sometimes sudden power outages will of course be a problem and loss for the company. Therefore, the use of Automatic Transfer Switch (ATS) and Automatic Generator Start (AGS) is the main technology in electrical automation systems to maintain power reliability. ATS operates on the front line when the power goes out, automatically switching from the main power source to a backup generator in a matter of seconds, ATS ensures that the electricity load will continue to be supplied without any interruption. Meanwhile, AGS will activate the electricity generator automatically when there is a power outage or disruption to the main power source. This system is important to ensure that the backup generator is activated when needed to meet the company's electricity needs.